EU Antidumping Cases against China: An Overview and Future Prospects with Respect to China's WTO Membership - Xiang Liu; Hylke Vandenbussche (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2002)
Since 1979, when the first antidumping case against China was initiated by the European Union, the EU has lodged nearly 90 antidumping proceedings against China by the end of 2000. China by now, has become the country most accused of dumping by the EU. Most of the antidumping suits have led to relatively high duties on Chinese products. This paper explores the characteristics and the trends of EU antidumping actions against China over the past two decades and provides a comprehensive analysis of the factors that have led to China's vulnerability to EU antidumping charges. Some future prospects with respect to China's membership of WTO are also presented.
Keywords: L11; L12; L13; D42; D43; 330; EU antidumping; China; WTO; monopoly; oligopoly; Antidumping; Internationale Wirtschaftsorganisation; Mitgliedschaft; EU-Staaten; China